Chemical Composition and the Feeding Value of Azolla (Azolla pinnata) Meal for Egg-Type Chicks - Alalade, O.A.; Iyayi, E.A. (International Journal of Poultry Science, 2006)
Biochemical and nutritional studies were carried out to evaluate the potential of Azolla (Azolla pinnata R. Brown) meal, AZM, as a feed resource in the diet of egg-type chicks. In a completely randomized design, 30 two weeks old Nera brown chicks were assigned to each of the four dietary treatments containing 0, 5, 10 and 15% azolla meal. Chemical analysis indicated that azolla meal contained (%DM) 21.4 crude protein, 12.7 crude fibre, 2.7 ether extract, 16.2 ash and 47.0 carbohydrate. A gross energy value of 2039 kcal kg-1 was obtained. The concentrations of calcium, phosphorus, potassium and magnesium were 1.16%, 1.29%, 1.25% and 0.25% respectively, while those of sodium, manganese, iron, copper and zinc were 23.79ppm, 174.42ppm, 755.73ppm, 16.74ppm and 87.59ppm respectively. The chemical score index showed the potential of azolla meal as a good source of protein. Leucine, lysine, arginine and valine were the predominant essential amino acids while tryptophan and the sulphur-containing amino acids were deficient. All AZM diets depressed feed intake. Average weekly weight gains (AWWG) were 95.43g, 95.22g, 98.62g and 93.44g for 0, 5, 10 and 15% AZM respectively. Average weekly feed intake decreased (p< 0.05) from 286.95g/bird to 224.38g/bird as the level of AZM increased to 15%. A non-statistically better AWWG of 98.62g and feed conversion ratio (FCR) of 2.54 was obtained on diet containing 10% AZM. Based on these results, AZM, as an unconventional feed resource has a potential as a feedstuff for chicks. Above all, for improved performance, diets of chicks can be formulated with inclusion of AZM up to 10%.